The Edinburgh companion to contemporary Scottish poetry - McGuire, Matt, 1977-; Nicholson, Colin (Edinburgh companions to Scottish literature., 2009)
The last three decades have seen unprecedented flourishing of creativity across the Scottish literary landscape, so that contemporary Scottish poetry constitutes an internationally renowned, award-winning body of work. At the heart of this has been the work of poets. As this poetry makes space for its own innovative concerns, it renegotiates the poetic inheritance of preceding generations. At the same time, Scottish poetry continues to be animated by writing from other places. The Edinburgh Companion to Contemporary Scottish Poetry is the definitive guide to this flourishing poetic scene. Its chapters examine Scottish poetry in all three of the nation's languages. It analyses many thematic preoccupations: tradition and innovation; revolutions in gender; the importance of place; the aesthetic politics of devolution. These chapters are complemented by extended close readings of the work of key poets that have defined this era, including Edwin Morgan, Kathleen Jamie, Don Paterson, Aonghas MacNeacail and John Burnside. Key Features A thorough guide to contemporary Scottish poetry and poets, making the book an ideal course text Reflects the ways in which the work of Scottish poets reflects a radical cultural independence following Devolution Provides authoritative essays by the leading experts in the field Includes a valuable synoptic bibliography